Investigating the Influencing Factors of the Entrepreneurial Ecosystem in Sports Enterprises: A Case Study Approach - Chunfang Li (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In the past decade, the study of entrepreneurial ecosystems has garnered increasing attention, with scholars examining aspects such as conceptual meanings, operational mechanisms, and entrepreneurial environments. The entrepreneurial journey, particularly within the sports industry, is fraught with unique challenges and the potential for abrupt terminations. This makes the investigation of the factors influencing the entrepreneurial ecosystem in sports enterprises especially crucial. This paper delves into the specific dynamics of the sports entrepreneurial ecosystem by utilizing case studies of prominent sports companies. It employs the entropy weight method to analyze and prioritize the influencing factors within this sector. The findings aim to provide valuable insights and recommendations for current and future participants in the sports entrepreneurial ecosystem, facilitating a deeper understanding of its unique challenges and opportunities. This research highlights the critical factors that support or hinder sports-related ventures and contributes to the broader discourse on entrepreneurship in niche markets.